Analisa Kadar Asam Lemak Bebas Dalam Minyak Goreng Curah Secara Alkalimetri - Rosa Mardiana; Azmalina Andriani; Fathur Ridha (Journal of Pharmaceutical and Health Research, 2020)
Bulk cooking oil is cooking oil produced from palm oil, which is filtered only once so that the color looks different from clearer branded cooking oil. The repeated use of oil experiences oil destruction or damage caused by oxidation and hydrolysis processes that break down oil molecules into acids. This process gets bigger with high heating and long time during food frying. The research method used in this study uses a systematic sampling technique of random sampling, and data processing using the alkalimetry method. The results of the analysis of free fatty acids in Alcalimetrid bulk cooking oil in 50 ml ethanolutanol obtained levels of 0.68%, 0.53%, 0.43%. While in 75 ml ethanol ethanol were 0.86%, 0.64%, 0.52%. In the principle of analysis of free fatty acid levels with a strong base pH of the solution at an equivalent point above 8-10, the indicator used phenolphthalein will occur pink at the endpoint of the titration. From the results of the analysis of free fatty acid levels obtained from the three bulk cooking oil agents showed that the oil quality was not good for use because it caused a high auto-oxidation process. The process of autooxidation is the absorption of oxygen in the air by oil. So it can be concluded that the higher the level of free fatty acids, the higher the absorption of oxygen so that it can affect the taste of the oil, for example, oil is rancid. And if consumed with a long time will cause the emergence of cholesterol, coronary heart disease, cough, and sore throat